Reproductive characteristics of the hermaphroditic four-finger threadfin, Eleutheronema tetradactylum (Shaw, 1804), in tropical coastal waters - Kay Khine Soe; Teuku Haris Iqbal; Apiradee Lim; Wen‑Xiong Wang; Karl W. K. Tsim; Yutaka Takeuchi; Nirattisai Petchsupa; Sukree Hajisamae (BMC Zoology, 2023)
Abstract This study investigated the reproductive traits of the hermaphroditic four-finger threadfin, Eleutheronema tetradactylum, along the coasts of Thailand during January to December 2021. Fish samples were collected from Pattani Bay, Thailand to assess the sex ratio, gonadosomatic index (GSI), maturity stage and fecundity. Additional fish samples were also collected from other areas to evaluate the length and weight at first sex change (Ls50 and Ws50) and length at first maturity (Lm50). The overall sex ratio for male and female was 1:0.69 with male being predominant throughout the year. Threadfin fish spawn the whole year round with peaks during moderate rainy and heavy rainy seasons. Histological examination confirmed its protandrous hermaphrodite posing multiple spawning habits. The average fecundity was 1.85 × 105 ± 1.05 × 105 eggs and positively related with standard length, body weight, gonad weight, and egg diameter (p < 0.05). The Ls50 and Ws50 were 27.58 cm and 419.39 g, and 29.71 cm and 457.28 g, for fish from Pattani Bay and Samut Prakan province, respectively. The Lm50 of male from Pattani Bay and Samut Prakan province were 25.78 cm and 25.56 cm, respectively, which were larger than those from Satun and Nakhon Sri Thammarat provinces. The Lm50 of females from Pattani Bay was smaller than that from Samut Prakan province. This study provided fundamental information on the reproductive characteristics of E. tetradactylum, which can be implemented to support management of natural fish stock and aquaculture development.